2021
DOI: 10.3389/fendo.2021.686054
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Genome Interactions Identify Potential Adipocyte Metabolism-Associated Gene STON1 and Immune-Correlated Gene FSHR at the rs13405728 Locus in Polycystic Ovary Syndrome

Abstract: Backgroundrs13405728 was identified as one of the most prevalent susceptibility loci for polycystic ovary syndrome (PCOS) in Han Chinese and Caucasian women. However, the target genes and potential mechanisms of the rs13405728 locus remain to be determined.MethodsThree-dimensional (3D) genome interactions from the ovary tissue were characterized via high-through chromosome conformation capture (Hi-C) and Capture Hi-C technologies to identify putative targets at the rs13405728 locus. Combined analyses of eQTL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…et al carried out a deep, complex genetic functional analysis (3D genome interactions based on high-throughput chromosome conformation capture technology (Hi-C), eQTL, RNA-Seq, DNase-Seq, ChIP-Seq, and sing-cell sequencing) proving the relationship of STON1-coexpressed genes (PPP1R21, LHCGR, FOXN2, STON1-GTF2A1L, GTF2A1L, etc.) with metabolic processes in adipocytes (p = 0.0001), which was confirmed in the adipose tissue (p < 0.0001) and ovaries (p = 0.0035) of mice fed on fats [119]. The authors also revealed pronounced, multidirectional, sex-specific correlations between the expression of STON1 and BMI in male and female adipocyte tissue: In male adipocytes, BMI positively correlated with the STON1 expression, but in female adipocytes, these correlations were negative [119].…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…et al carried out a deep, complex genetic functional analysis (3D genome interactions based on high-throughput chromosome conformation capture technology (Hi-C), eQTL, RNA-Seq, DNase-Seq, ChIP-Seq, and sing-cell sequencing) proving the relationship of STON1-coexpressed genes (PPP1R21, LHCGR, FOXN2, STON1-GTF2A1L, GTF2A1L, etc.) with metabolic processes in adipocytes (p = 0.0001), which was confirmed in the adipose tissue (p < 0.0001) and ovaries (p = 0.0035) of mice fed on fats [119]. The authors also revealed pronounced, multidirectional, sex-specific correlations between the expression of STON1 and BMI in male and female adipocyte tissue: In male adipocytes, BMI positively correlated with the STON1 expression, but in female adipocytes, these correlations were negative [119].…”
Section: Discussionmentioning
confidence: 65%
“…with metabolic processes in adipocytes (p = 0.0001), which was confirmed in the adipose tissue (p < 0.0001) and ovaries (p = 0.0035) of mice fed on fats [119]. The authors also revealed pronounced, multidirectional, sex-specific correlations between the expression of STON1 and BMI in male and female adipocyte tissue: In male adipocytes, BMI positively correlated with the STON1 expression, but in female adipocytes, these correlations were negative [119]. The features of circulating STON1-GTF2A1L RNA expression in epicardial adipose tissue in individuals with/without heart failure were shown in the work of He S. et al [121].…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations